PENGARUH KORUPSI, DEMOKRASI DAN POLITIK TERHADAP KEMISKINAN DI DELAPAN NEGARA ASEAN DENGAN PERTUMBUHAN EKONOMI SEBAGAI VARIABEL MODERASI - Yolanda Yolanda (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims the influence of corruption, democracy and politics on poverty in ASEAN countries with economic growth as a moderating variable. The method used is using the panel regression model. This data uses a combination method between time series data from 2013 - 2016 and a cross section consisting of 8 countries. Data obtained from World Bank annual reports, Transparency International and Freedom House. The results of this study indicate that (1) Corruption Perception Index (CPI) has a significant and negative effect on poverty, meaning that if the CPI increases then poverty will decrease (2) Democracy has no significant and negative effect on poverty. This means that if democracy increases, poverty will decrease (3) Politics has a significant and negative effect on poverty, meaning that if politics increases, poverty will decrease (4) Economic growth has a significant and positive effect on poverty, meaning if economic growth increases then poverty will decline (3) Economic growth unable to moderate the relationship between corruption, democracy and politics towards poverty in 8 ASEAN countries. Economic growth as an interaction variable is a predictor variable (Predictor Moderate Variable), which means that economic growth is only an independent variable.